2001
DOI: 10.1002/ccd.1228
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral artery stenting

Abstract: The safety and efficacy of endoluminal stenting in treating atherosclerotic vertebral artery disease was evaluated in 38 vessels in 32 patients. Indications for revascularization included diplopia (n = 4), blurred vision (n = 4), dizziness (n = 23), transient ischemic attacks (n = 4), drop attack (n = 1), gait disturbance (n = 1), headache (n = 2), and asymptomatic critical stenosis (n = 1). Success (< 20% residual diameter stenosis, without stroke or death) was achieved in all 32 patients (100%). One patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(34 citation statements)
references
References 11 publications
0
34
0
Order By: Relevance
“…Hence, our findings suggest that vertebral stenosis patients with clinical features similar to those randomized in CAVATAS may have a low risk of recurrent vertebrobasilar territory stroke, even when treated with medical treatment alone. Previous case series showing a low rate of recurrent stroke after endovascular treatment of symptomatic vertebral stenosis have been interpreted as demonstrating effective stroke prevention, 13,15 but this conclusion must be open to question if our findings in the medical arm are a reflection of the true risk. However, it is possible that our results have been unduly affected by chance because of the small numbers of patients randomized.…”
Section: Discussionmentioning
confidence: 86%
“…Hence, our findings suggest that vertebral stenosis patients with clinical features similar to those randomized in CAVATAS may have a low risk of recurrent vertebrobasilar territory stroke, even when treated with medical treatment alone. Previous case series showing a low rate of recurrent stroke after endovascular treatment of symptomatic vertebral stenosis have been interpreted as demonstrating effective stroke prevention, 13,15 but this conclusion must be open to question if our findings in the medical arm are a reflection of the true risk. However, it is possible that our results have been unduly affected by chance because of the small numbers of patients randomized.…”
Section: Discussionmentioning
confidence: 86%
“…185,186 Retrospective case series have shown that the procedure can be performed with a high degree of technical success. [187][188][189][190] Long-term follow-up data are limited, and further randomized studies are needed to more clearly define evidence-based recommendations in this setting.…”
Section: B Extracranial Vertebrobasilar Diseasementioning
confidence: 99%
“…Medical, surgical, and endovascular methods are used in the treatment of VA stenoses (4,5). Endovascular treatment should be considered as a first-line option for patients with posterior system strokes that develop despite appropriate medical treatment or for patients who have asymptomatic bilateral carotid occlusion and in whom collateral circulation is provided only through VA (6, 7).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, stents cut from a tube were used to prevent breakage in the orifice lesions due to the angulation of VA with subclavian artery, while balloon expandable stents are used today. Drug-releasing stents may also reduce restenosis in this region where restenosis is more prominent (5,14,19). VA balloon angioplasty and anticoagulant and antithrombotic treatment protocols as a medical therapy after stenting are the standard applications indicated in the literature (20,21).…”
Section: Discussionmentioning
confidence: 99%